Cost-Effectiveness Analysis Of Biomarker-Based And Risk-Based Screening In Early Detection Of Preeclampsia: Systematic Review - Aurellia Saraswati Winahyu Naiaputri (CV. AFDIFAL MAJU BERKAH, 2026)
Preeclampsia is one of the leading causes of maternal morbidity and mortality, especially in developing countries. Evaluation of the cost-effectiveness of first-trimester screening is essential to ensure accurate and efficient interventions. The objective of this review is to examine and compare the cost-effectiveness between biomarker-based preeclampsia screening and maternal risk-based screening in the first trimester of pregnancy. This study used a systematic review method based on the PRISMA guidelines. Articles searched through PubMed and ScienceDirect with a range of 2020–2025. Quality assessment using the CHEERS Checklist. Five studies were included in this review. All studies show that first-trimester preeclampsia screening is a cost-effective, even cost-saving strategy, especially when combined with early aspirin. Biomarker-based screening and risk algorithms are more cost-efficient than conventional screening. These results can be the basis for the formulation of maternal health policies in Indonesia. Preeclampsia, first trimester screening, cost-effectiveness, biomarkers.